Antitumor effectiveness of bleomycin on SA-1 tumor after pretreatment with vinblastine - Čemažar, Maja (Radiology and oncology (Ljubljana), 2000)
In our previous study, vinblastine (VLB) was shown to increase the plasma membrane fluidity. This effect of VLB might be exploited for better transport of drugs through the plasma membrane. The aim of the present study was to determine whether pretreatment with VLB can increase the cytotoxic effect of BLM on intraperitoneal SA-1 tumors in mice. Materials and methods. BLM and VLBwere used as single agents or in various combinations, i.e. BLM injected 24h before VLB or vice-versa, VLB injected 24 h before BLM. Cell and animal survival together with DNA histograms were the end-points used to determine the effect of these combined treatments. Results. Both drugs, either as singletreatment or in different combined therapy schedules reduced significantly the number of cells in peritoneal lavage, compared to control, saline treated animals. The combination of VLB, followed by BLM after 24 h reduced significantly the number of cells in peritoneal lavage, compared to the treatment in which BLM was followed by VLB or to the treatment with singledrugs alone. Median survival time of mice treated with VLB alone, BLM alone and combination of both drugs was significantly prolonged compared to the control untreated mice. When VLB and BLM were combined, both treatment combinations were more effective than monochemotherapies with VLB or BLM. The best results were obtained when VLB was followed by BLM after 24 h. The DNA histogram of cells treated with VLB showed a decreased number of cells in S phase and an increased number of cells with DNA values greater than in G2M compartment compared to the control untreated cells. BLM in the dosage used inthese experiments did not affect the progression of cells through cell cycle. Both combinations of VLB and BLM produced similar cell kinetic effect as VLB alone. Conclusion. (Abstract truncated at 2000 characters.)
Keywords: bleomicin; Bleomycin; Cell survival; Drug therapy; Fibrosarcoma; Flow cytometry; Mice; Peritoneal lavage; rak (medicina); Sarcoma, experimental; Survival rate; Vinblastine; zdravljenje